On the Geometric Mean Index: A Note - Brennan, Michael J.; Schwartz, Eduardo S. (Journal of Financial and Quantitative Analysis, 1985)
This note explores the properties of some stock markets indices that are claimed to approximate a continuously rebalanced equally weighted portfolio.